THU0468 The Use of Anti-Tnf Therapy in Uveitis Refractory to Immunosuppressive Drugs in a Multidisciplinary Consult. (23rd January 2014) - Franco Gomez, K. N.; Peiteado, D.; Cajigas, D.; Lojo, L.; Castillo, C.; Garcia, S.; Alcocer, P.; Plasencia, C.; Schilincker, A.; Martin Mola, E.
Abstract : Background: Since its discovery biological therapies have been used for the treatment of immune and inflammatory diseases such as uveitis. Anti-TNF therapy has played an important role in this area. Objectives: This is a retrospective study that evaluates the use of anti-TNF therapy in the treatment of uveitis refractory to oral glucocorticoids and immunosuppressive drugs. Methods: In a multidisciplinary consult of uveitis we included patients with idiopathic, immune mediated or non infectious uveitis treated with Anti-TNF agents in the last 10 years. We analyzed the efficacy of Infliximab (5 mg / kg / iv in 0, 2, and 6 weeks and then every 8 weeks) and Adalimumab (40 mg every 2 weeks). Patients with uveitis associated with SpondyloArthritis in which the Anti-TNF agent was initially used for the control of joint symptoms were excluded. We analyzed the response to treatment by measuring changes in visual acuity, inflammatory activity (presence of vitritis, vasculitis, coroideoretineal infiltrate and macular edema), and the reduction or withdrawal of oral glucocorticoids after the initiation of the Anti-TNF agent. Results: A total of 13 patients (18 affected eyes) with a mean age of 43.15 (range 26-64 years) were included. 6 patients had posterior uveitis secondary to Behçet disease, 2 Vogt Koyanagi Harada disease (VKH), 2 scleritis / episcleritis, 1 recurrent anterior uveitis in a patient with SpondyloArthriti associated with inflammatory bowel disease, 1 Birdshot chorioretinopathy and 1 idiopathic panuveítis. All patients were treated prior to Anti-TNF therapy with oral glucocorticoids and immunosuppressive drugs. 11 patients (84%) were initially treated with Infliximab (5 with a short cycle of three doses at weeks 0, 2, and 6, and the rest continued infusions every 8 weeks) and 2 (15%) with Adalimumab. 3 of the patients treated with Infliximab (23%) required change to Adalimumab, all of them due to adverse drug reactions. 61% of patients had an improvement in visual acuity with an average of 0.4 (± 0.2) and 92% improved in inflammatory activity. In 7 patients (53%) both parameters improved. All the patients that received a short cycle of Infliximab relapsed in two years, in this group 1 patient with Behçet made ​​a second short cycle, with good response but was lost in the follow up, a second patient decided to restart and maintain the Anti-TNF agent continuously and the other 3 were changed to immunosuppressive drugs. Only 1 of the patients with a steady dose of Infliximab relapsed. Glucocorticoids were completely suspended in 5 patients and decreased in another 5 patients. No serious side effects were observed in this case series. Conclusions: Infliximab and Adalimumab are effective in the treatment and control of inflammatory activity in patients with uveitis refractory to oral glucocorticoids and immunosuppressive drugs. In patients with short cycles, relapse was observed after discontinuation, requiring to continue treatment with immunosuppressive drugs or to change to another Anti-TNF. Disclosure of Interest: None Declared